Developing an ELT Instructional Model for Vocational High Schools Students at Tourism Zones - Irawan, Lalu Ari; Oral Frank, Tina; Dehghani, Sadaf (Journal of Language and Literature Studies, 2022)
Indonesian Economic Development has become a gate to Bali and Lombok for international visitors. Recently, the Lombok tourism development has established a refinement after facing serial earthquakes. In the statistic for the tourism year 2016, there were 3.1 million tourists coming to Lombok. In addition, 3.8 million people were targeted to come to Lombok in the year 2020. In other words, Lombok promotes the highest contribution to the national government economy. Because of these issues, the vocational high schools which have tourism study programs should lead their students in foreign language communication, English. Teaching English for a specific purpose needs a precise instructional model because ELT teachers apply the ELT model for different objectives. Therefore, learners study English for different purposes. For vocational high school students, they learn English to help them to communicate in the workplace. Because of this, they are directed to have communicative competence. In senior or junior high schools, scientific-based instruction has been applied to help students learn English and even other subjects. This instruction is considered as a solution for them to have not only linguistic competencies but also communicative skills. Therefore, this study will be aimed at developing an instructional model for vocational high school students in tourism zones. This study applied the procedural research and development (R&D) design. The R&D design follows the Borg & Gall and David design, which consists of pre-development and development stages. The product of this study was an instructional model, namely the tourism-based instructional (TBI) model for vocational high school students in the tourism zones.